Relationship between Breastfeeding Self-Efficacy and Exclusive Breastfeeding at the Taman Krocok Health Center - maryanti, syiska atik; Devianti, Elisa Tiara; Palupi, Jenie (D'Nursing and Health Journal (DNHJ), 2024)
ABSTRACT Background: Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, a decrease from 69.7% in the previous year 2021. In East Java Province, exclusive breastfeeding coverage in several districts is also still quite low, including Bondowoso City (35.8%). According to the Bondowoso District Health Office, the exclusive breastfeeding coverage of Bondowoso District in 2022, there is one sub-district that has a low exclusive breastfeeding status, namely the working area of the Taman Krocok Bondowoso Health Center. This study aims to determine the relationship between breastfeeding self-efficacy and exclusive breastfeeding. Method: This research design uses analytic with Crossectional approach. The sample in the study amounted to 65 mothers who had toddlers 6-12 months, using purposive sampling technique. Data collection using a questionnaire sheet. Data analysis with Chi-Square test. Results: 61.54% of respondents had high BSE, 38.46% had low BSE. There is an association between BSE and exclusive breastfeeding with ρ-value = 0.001 < α 0.05. Conclusion: One of the causes that affects mothers in providing exclusive breastfeeding is the level of maternal confidence (Breastfeeding Self - Efficacy) in breastfeeding their babies.